Water-Soluble Fluorinated and PEGylated Cyanostilbene Derivative: An Amphiphilic Building Block Forming Self-Assembled Organic Nanorods with Enhanced Fluorescence Emission - Shin, Seunghoon; Gihm, Se Hoon; Park, Chong Rae; Kim, Sehoon; Park, Soo Young (AMER CHEMICAL SOC, 2013)
We report synthesis and optical/structural characterization of new fluorescent rod-coil amphiphiles based on the PEGylated alpha-cyanostilbene skeleton (12EO-CNMBE and 12EO-CNTFMBE) and their self-assembly behaviors in water. Distinct from the common amphiphilic behavior of nonfluorinated 12EO-CNMBE forming spherical nanostructures, fluorinated 12EO-CNTFMBE has proven to be the first example of a molecular building block that can self-assemble in water into small-dimension, small-aspect-ratio organic nanorods with aggregation-induced enhanced emission (AIEE). The robust structural integrity and hydrophobic/pi-conjugated nature of the fluorinated block assembly, as well as the antifouling coating by the hydrophilic PEG block, enabled stable encapsulation of a model drug (Nile Red) within the self-assembled nanorod structure and its successful delivery through membrane filters. By virtue of these advantageous attributes along with high intracellular uptake efficiency, the 12EO-CNTFMBE nanorods manifested potential as a seff-signaling fluorescent nanocarrier for the intracellular delivery of hydrophobic cargos.
Keywords: DRUG-DELIVERY; SPECTROSCOPY